Improving Students' Ability to Solve HOTS-Based Mathematics Problems with Problem-Solving Theory from Polya - Efi Maysaroh; Sri Sutarni (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2023)
This study aims to describe the improvement of students' ability to solve HOTS-based mathematics problems with the theory of problem-solving from Polya. This study used classroom action research. Data collection techniques use interviews, tests, observations, documentation, and field notes. Data analysis techniques use a flow method consisting of data reduction, data presentation, and data verification. The results showed a classical improvement in students' ability to solve HOTS-based math problems, it can be seen that each indicator reaches a targeted percentage of â‰¥60%, starting from before the action to the second cycle of action. Thus, the conclusions of this study show that Polyaâ€™s problem-solving theory can improve students' ability to solve HOTS-based math problems.